PENGARUH APLIKASI FOTOYU TERHADAP MOTIVASI JOGGING GENERASI Z DI KAWASAN BLANG PADANG KOTA BANDA ACEH - Elisa Hayati; Ahmad Nasriadi; Zikrur Rahmat (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2026)
This study aims to determine the level of FotoYu application use, the level of jogging motivation, and the influence of the FotoYu application on the jogging motivation of Generation Z in the Blang Padang area, Banda Aceh City. This study used a quantitative approach with an explanatory research design. The sample consisted of 100 Generation Z respondents aged 17-26 years, determined through purposive sampling based on the Lemeshow formula. Data were collected using a five-point Likert scale questionnaire comprising nine items for the FotoYu Application variable and seven items for the Jogging Motivation variable, then analyzed using validity, reliability, classical assumption, and simple linear regression tests with SPSS version 26. The results showed that the level of FotoYu application use was in the high category (M = 3.59), and the level of jogging motivation was also in the high category (M = 3.76). Regression results indicated that the FotoYu Application had a positive and significant effect on Jogging Motivation, with a regression coefficient of 0.988, a t-count of 24.066 (t-table 1.984), and a significance value of 0.000 ( 0.05), leading to rejection of the null hypothesis. The coefficient of determination (R² = 0.855) indicated that 85.5% of the variation in jogging motivation could be explained by FotoYu application use. These findings support the Technology Acceptance Model and Social Cognitive Theory, suggesting that ease of technology use and digital social reinforcement can encourage active exercise behavior. This study recommends developing visual-based sports application features that better consider user privacy and data security.